USING PHRASES IN TEACHING AND LEARNING ENGLISH LANGUAGE.: Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
This article demonstrates information about the importance of English phrases and how to learn and teach them. Also there are given examples with meaning of phrases in this article.